2r=R
Because 2 of "r" make 1 R
Here’s your answer lemme know if it’s not clear
Answer: 1/6
Step-by-step explanation:
1/2 divided by 3/1 turns into 1/2 x 1/3 and when multiplying numerators and denominators with each other, you get 1/6.
<span>4x</span>² <span>+ 13x + 3=
4x</span>² + 12x + x + 3 =
4x(x+3) + (x+3) =
(4x+1)(x+3)
Answer:
<h3>
f(x) = 5x² + 2x</h3><h3>
g(x) = 6x - 6</h3>
Step-by-step explanation:
![\dfrac{5x^3-8x^2-4x}{6x^2-18x+12}\\\\6(x^2-3x+2)\ne0\ \iff\ x=\frac{3\pm\sqrt{9-8}}{2}\ne0\ \iff\ x\ne2\ \wedge\ x\ne1\\\\\\\dfrac{5x^3-8x^2-4x}{6x^2-18x+12}=\dfrac{x(5x^2-8x-4)}{6(x^2-3x+2)}=\dfrac{x(5x^2-10x+2x-4)}{6(x^2-2x-x+2)}=\\\\\\=\dfrac{x[5x(x-2)+2(x-2)]}{6[x(x-2)-(x-2)]} =\dfrac{x(x-2)(5x+2)}{6(x-2)(x-1)}=\dfrac{x(5x+2)}{6(x-1)}=\dfrac{5x^2+2x}{6x-6}\\\\\\f(x)=5x^2+2x\\\\g(x)=6x-6](https://tex.z-dn.net/?f=%5Cdfrac%7B5x%5E3-8x%5E2-4x%7D%7B6x%5E2-18x%2B12%7D%5C%5C%5C%5C6%28x%5E2-3x%2B2%29%5Cne0%5C%20%5Ciff%5C%20x%3D%5Cfrac%7B3%5Cpm%5Csqrt%7B9-8%7D%7D%7B2%7D%5Cne0%5C%20%5Ciff%5C%20x%5Cne2%5C%20%5Cwedge%5C%20x%5Cne1%5C%5C%5C%5C%5C%5C%5Cdfrac%7B5x%5E3-8x%5E2-4x%7D%7B6x%5E2-18x%2B12%7D%3D%5Cdfrac%7Bx%285x%5E2-8x-4%29%7D%7B6%28x%5E2-3x%2B2%29%7D%3D%5Cdfrac%7Bx%285x%5E2-10x%2B2x-4%29%7D%7B6%28x%5E2-2x-x%2B2%29%7D%3D%5C%5C%5C%5C%5C%5C%3D%5Cdfrac%7Bx%5B5x%28x-2%29%2B2%28x-2%29%5D%7D%7B6%5Bx%28x-2%29-%28x-2%29%5D%7D%20%3D%5Cdfrac%7Bx%28x-2%29%285x%2B2%29%7D%7B6%28x-2%29%28x-1%29%7D%3D%5Cdfrac%7Bx%285x%2B2%29%7D%7B6%28x-1%29%7D%3D%5Cdfrac%7B5x%5E2%2B2x%7D%7B6x-6%7D%5C%5C%5C%5C%5C%5Cf%28x%29%3D5x%5E2%2B2x%5C%5C%5C%5Cg%28x%29%3D6x-6)